Prior Tonsillectomy and the Risk of Breast Cancer in Females: A Systematic Review and Meta-analysis - Kacimi, Salah Eddine O.; Elgenidy, Anas; Cheema, Huzaifa Ahmad; Ould Setti, Mounir; Khosla, Atulya Aman; Benmelouka, Amira Yasmine; Aloulou, Mohammad; Djebabria, Kawthar; Shamseldin, Laila Salah; Riffi, Omar; Mesli, Nabil Smain; Sekkal, Hanane Z.; et al. (Frontiers in Oncology, 2022)
Background Exposure to recurrent infections in childhood was linked to an increased risk of cancer in adulthood. There is also evidence that a history of tonsillectomy, a procedure often performed in children with recurrent infections, is linked to an increased risk of leukemia and Hodgkin lymphoma. Tonsillectomy could be directly associated with cancer risk, or it could be a proxy for another risk factor such as recurrent infections and chronic inflammation. Nevertheless, the role of recurrent childhood infections and tonsillectomy on the one hand, and the risk of breast cancer (BC) in adulthood remain understudied. Our study aims to verify whether a history of tonsillectomy increases the risk of BC in women. Methods A systematic review was performed using PubMed, Google Scholar, Scopus, Embase, and Web of Science databases from inception to January 25, 2022, to identify the studies which assessed the association between the history of tonsillectomy and BC in females. Odds ratio (OR) was calculated using the random/fixed-effects models to synthesize the associations between tonsillectomy and BC risk based on heterogeneity. Results Eight studies included 2252 patients with breast cancer of which 1151 underwent tonsillectomy and 5314 controls of which 1725 had their tonsils removed. Patients with a history of tonsillectomy showed a higher subsequent risk of developing BC (OR, 1.24; 95% CI: 1.11-1.39) as compared to patients without a history of tonsillectomy. Influence analyses showed that no single study had a significant effect on the overall estimate or the heterogeneity. Conclusions Our study revealed that a history of tonsillectomy is associated with an increased risk of breast cancer. These findings underscore the need for frequent follow-ups and screening of tonsillectomy patients to assess for the risk of BC.